Daughters of Abraham : feminist thought in Judaism, Christianity, and Islam - Haddad, Yvonne Yazbeck, 1935-; Esposito, John L. (University Press of Florida, 2001)
Annotation "Important for a general audience interested in women and religion, this book will be especially valuable to scholars in the fields of feminist theology, comparative religion, and interfaith studies."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved
Keywords: Women in Judaism.; Feminism -- Religious aspects -- Judaism.; Women in Christianity.; Feminism -- Religious aspects -- Christianity.; Women in Islam.; Feminism -- Religious aspects -- Islam.; Femmes dans le judaïsme.; Féminisme -- Aspect religieux -- Judaïsme.; Femmes dans le christianisme.; Féminisme -- Aspect religieux -- Christianisme.; Femmes dans l'islam.; Féminisme -- Aspect religieux -- Islam.; RELIGION -- Comparative Religion.; Feminism -- Religious aspects -- Christianity; Feminism -- Religious aspects -- Islam; Feminism -- Religious aspects -- Judaism; Women in Christianity; Women in Islam; Women in Judaism; Christentum; Feminismus; Feministische Theologie; Frau; Islam; Judentum; Feminisme.; Jodendom.; Christendom.; Islam.